Evaluasi Tingkat Keberhasilan Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan Pertanian (PNPM MPd Pertanian) Terhadap Komoditi Kakao Rakyat Di Kampung Abreso Distrik Ransiki Kabupaten Manokwari Selatan - Supri Hadi; Titirloloby, Marsina; Hutabarat, Martua (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2014)
This study aimed to evaluate the success of development programs cocoa plantation crop people committed by the National Program for Community Empowerment in Kampung Abreso, by looking at the activities are divided into three (three) categories, namely (1) Community Capacity Development Activities; (2) The Agricultural Development; and (3) Activities Supporting Development of Agricultural Infrastructure. The method used is descriptive method with a case study. The selection of respondents census conducted by the researcher to farmer groups totaling 29 heads of families, so that the collected data is analyzedby tabulation. The research techniques used in the data collection is the primary data and secondary data. The results of this study showed that the activities undertaken by the PNPM MPd Agricultural considered not successful because not all farmers involved in community development activities, as well as procurement or distribution of agricultural implements such as fertilizers, medicines, seeds and agricultural tools small (APK ) and the provision of infrastructure and post-harvest crop is not appropriate and does not split evenly according to the needs of farmers to support agricultural development and agricultural infrastructure support activities.